The Effect of Various Exercises for the Most Important Psychological Variables According to Cognitive Achievement in Developing Some Basic Skills for Young Footballers - Mousa, Hayder Jaber; Jassam, Dhiaa Rehman; Alhmdni, Thulfiqar Abdulameer Sulaiman (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to reveal the various exercises for the most important psychological variables according to the cognitive achievement in developing some basic skills for youth in football. The research hypotheses were of significant differences in the level of skill performance between the two research groups and for the benefit of students, who are learning according to the various exercises for the most important psychological variables. The researchers used the experimental method, and the sample of the research consisted of (40) youth players / Najaf Sports Club, and they were divided into two experimental and control groups, and methods and tools were used to collect information, and then the researchers used statistical methods, including (spss), and the researchers concluded that the various exercises are important to them. Psychological variables, according to cognitive achievement, have a positive effect in developing the basic skills under research, and the most important recommendations were to emphasize the use of various exercises for the most important psychological variables in learning the most important basic skills for young football players. So, the need for change and diversification in educational and training methods because of its great importance in enriching the learning process.